A sodium ion battery positive electrode material and its preparation method and application
The atomic layer deposition method forms a dense sodium metaaluminate coating on the surface of the positive electrode material of the sodium ion battery, which solves the stability problem of the material when exposed to air and significantly improves the cycling performance and stability of the battery.
Patent Information
- Application Number
- CN202211649978.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-21
AI Technical Summary
When the layered transition metal oxide positive electrode material of sodium ion battery is exposed to air, sodium ions will be removed and water will be embedded, resulting in a degradation of battery circulation and rate performance and severe damage to the material structure.
The atomic layer deposition method is used to coat and modify the surface of the positive electrode material of the sodium ion battery, and deposit it with aluminum source gas phase precursor, sodium source gas phase precursor and water vapor to form a dense and uniform sodium metaaluminate coating layer, avoiding the damage to the material by the aqueous phase coating method.
It significantly improves the circulation performance of the positive electrode material of sodium ion battery, improves the stability of the material surface, prevents the removal of sodium ions and the embedding of water, and maintains the efficient performance of the battery.
Smart Images

Figure BDA0004010011740000111 
Figure BDA0004010011740000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries and lithium-ion batteries work on similar principles. They are both rocking-chair secondary batteries that rely on the intercalation and deintercalation of ions between positive and negative electrodes. Compared with lithium resources, sodium resources are quite abundant. The content of sodium in the earth's crust is more than four hundred times that of lithium. It has the advantages of being cheaper and more stable in terms of cost. In terms of performance, although the energy density of sodium-ion batteries is not as high as that of lithium-ion batteries, they have unique advantages in charge and discharge rate and low-temperature performance. After charging for 15 minutes at room temperature, 80% of the power can be achieved. When working in an environment of minus 20 degrees Celsius, the energy retention rate of sodium-ion batteries is close to 90%. Therefore, the application potential of sodium-ion batteries in the fields of new energy power batteries and large-scale energy storage has attracted much attention.
[0003] The cathode material is one of the key materials for sodium-ion batteries, which greatly affects the energy density and power density of the battery. x T m O2) materials are currently the main positive electrode materials for sodium ion batteries. However, when such materials are exposed to air, sodium ions will be released and water will be embedded. The sodium hydroxide formed on the surface by the release of sodium ions has extremely strong water absorption, which will further react with carbon dioxide to form an alkaline insulating layer, causing the battery cycle and rate performance to decline, and the structure of the material is seriously damaged. Therefore, it is necessary to coat and modify the surface of the sodium ion layered positive electrode material to solve the above problems. However, since the layered oxide materials of sodium ion batteries are very easy to absorb water, decompose and oxidize, post-treatment methods such as water washing of the materials and coating processes involving aqueous solutions cannot achieve coating modification.
[0004] Based on the above research, it is necessary to provide a method for preparing a positive electrode material for a sodium ion battery. The preparation method avoids the damage to the positive electrode material of the sodium ion battery by the aqueous phase coating method, and the obtained coating layer is dense and uniform, and the thickness is highly controllable. It can effectively alleviate the water absorption problem on the surface of the material without affecting the sodium ion insertion and extraction, thereby improving the cycle stability of the sodium ion battery. Summary of the invention
[0005] The object of the present invention is to provide a sodium ion battery positive electrode material and a preparation method and application thereof. The preparation method adopts atomic layer deposition for coating modification, does not involve an aqueous phase, can accurately control the thickness of the coating at the nanometer level, and compared with other coating methods, the obtained coating layer has high uniformity and high bonding strength with the core. It can be used as an effective means for coating and modifying the positive electrode material of the sodium ion battery, and significantly improves the cycle performance of the positive electrode material of the sodium ion battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0008] (1) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber, introducing an aluminum source gas phase precursor, a sodium source gas phase precursor and water vapor into the reaction chamber for atomic layer deposition, and completing a deposition process;
[0009] (2) Repeatedly introducing the reactants to realize the cycle of the deposition process described in step (1) to obtain the sodium ion battery positive electrode material with sodium aluminate coated on the surface.
[0010] The present invention adopts an atomic layer deposition method to in-situ coat sodium aluminate on the surface of the positive electrode material of the sodium ion battery. The entire coating process is carried out in the gas phase and is simple, controllable, green and pollution-free. The thickness of the coating layer can be precisely controlled at the nanometer level, thereby avoiding the damage of the positive electrode material of the sodium ion battery by the aqueous phase coating method. The obtained coating layer has high density, good uniformity, and is tightly combined with the core, effectively preventing a series of side reactions from occurring when the material is exposed to the air. While not affecting the deintercalation of sodium ions, the water absorption problem of the material surface is effectively alleviated, and the contact between the electrode material and the electrolyte is isolated during the cycle process, thereby improving the cycle performance of the battery.
[0011] The kernel of the present invention comprises Na x TMO2, TM includes transition metals, for example, any one of Ti, V, Cr, Mn or Cu or a combination of at least two thereof, x≤1, for example, 1, 0.8, 0.6, 0.4 or 0.2, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0012] Preferably, the temperature of the atomic layer deposition reaction chamber in step (1) is 210-250°C, for example, it can be 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C or 250°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] The temperature of the atomic layer deposition reaction chamber of the present invention affects the deposition effect. If the temperature of the atomic deposition reaction chamber is too high, the temperature of the deposition reaction is too high, and the deposited coating will decompose; if the temperature of the atomic deposition reaction chamber is too low, the temperature of the deposition reaction is too low, which is not conducive to the formation of the coating layer and the coating with ideal components cannot be prepared.
[0014] Preferably, the inner core in step (1) comprises a layered transition metal oxide.
[0015] Preferably, the order of introducing in step (1) is to first introduce the aluminum source gas phase precursor, then introduce the sodium source gas phase precursor, and finally introduce water vapor.
[0016] The invention introduces water vapor last, which can avoid the damage of water vapor to the core material and prevent water molecules from being embedded in the core. In addition, introducing the gas in this order can promote the in-situ generation of sodium aluminate and improve the bonding strength between the coating layer and the core.
[0017] Preferably, in step (1), the reaction chamber is evacuated before the gas is introduced into the reaction chamber.
[0018] Preferably, after the aluminum source gas phase precursor is introduced in step (1), purging is performed and then the sodium source gas phase precursor is introduced.
[0019] Preferably, after the sodium source gas phase precursor is introduced in step (1), it is purged and then water vapor is introduced.
[0020] Preferably, in step (1), purging is performed after the water vapor is introduced.
[0021] The present invention performs purging after each introduction of the reaction gas, which can further improve the uniformity of the coating, thereby further improving the cycle performance of the battery. If the purging described in the present invention is not performed, it will not only affect the generation of the reactants, but also cause the segregation of the coating layer elements, affecting the performance of the coating layer.
[0022] Preferably, the purge gas used for the purge includes nitrogen.
[0023] Preferably, the purge gas flow rate is 40-70 sccm, for example, 40 sccm, 45 sccm, 50 sccm, 55 sccm, 60 sccm, 60 sccm or 70 sccm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] The flow rate of the purge gas described in the present invention will affect the deposition effect of the coating layer. If the flow rate of the purge gas is too small, the precursor source cannot be purged cleanly, which will interfere with the reaction of the precursor source in the next step; if the flow rate of the purge gas is too large, it will cause gas waste.
[0025] Preferably, the purging time is 20-40 s, for example, 20 s, 25 s, 30 s, 35 s or 40 s, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the water vapor in step (1) is obtained by heating pure water at 98-105°C, for example, 98°C, 100°C or 105°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the time for introducing water vapor in step (1) is 1-3 s, for example, 1 s, 1.5 s, 2 s, 2.5 s or 3 s, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the water vapor flow rate in step (1) is 20-40 sccm, for example, 20 sccm, 30 sccm or 40 sccm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] The water vapor of the present invention participates in the reaction of the coating layer, and the time of its introduction will also affect the coating effect and the stability of the material.
[0030] Preferably, the aluminum source vapor phase precursor in step (1) is obtained by heating the aluminum source at 20-40°C, for example, it can be 20°C, 25°C, 30°C, 35°C or 40°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the aluminum source comprises trimethylaluminum and / or dimethylaluminum isopropoxide.
[0032] Preferably, the introduction time of the aluminum source gas phase precursor in step (1) is 0.5-2s, for example, 0.5s, 1s, 1.5s or 2s, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the flow rate of the aluminum source gas phase precursor in step (1) is 20-40 sccm, for example, 20 sccm, 30 sccm or 40 sccm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the sodium source gas phase precursor in step (1) is obtained by heating a sodium source at 160-180°C, for example, 160°C, 165°C, 170°C, 175°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the sodium source comprises sodium tert-butoxide / sodium acetoacetate.
[0036] Preferably, the time for introducing the sodium source gas phase precursor in step (1) is 1-3s, for example, 1s, 1.5s, 2s, 2.5s or 3s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the flow rate of the sodium source gas precursor in step (1) is 20-40 sccm, for example, 20 sccm, 30 sccm or 40 sccm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the thickness of the sodium ion battery positive electrode material in step (2) is 15-60 nm, for example, it can be 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm or 60 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] The present invention does not impose any specific limitation on the number of cycles in step (2), and the number of cycles can be adaptively adjusted according to the thickness of the coating layer.
[0040] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0041] (1) heating an aluminum source at 20-40° C. to obtain an aluminum source vapor precursor; heating a sodium source at 160-180° C. to obtain a sodium source vapor precursor; and heating pure water at 98-105° C. to obtain water vapor;
[0042] (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 210-250° C., evacuating the chamber, and then introducing an aluminum source gas phase precursor into the reaction chamber at a flow rate of 20-40 sccm for 0.5-2 seconds, and then introducing nitrogen at a flow rate of 40-70 sccm for purging for 20-40 seconds;
[0043] (3) After the purge in step (2) is completed, a sodium source gas precursor is introduced at a flow rate of 20-40 sccm for 1-3 seconds, and then nitrogen is introduced at a flow rate of 40-70 sccm for purging for 20-40 seconds;
[0044] (4) After the purge in step (3) is completed, water vapor is introduced at a flow rate of 20-40 sccm for 1-3 seconds, and then nitrogen is introduced at a flow rate of 40-70 sccm for purging for 20-40 seconds to complete a deposition process;
[0045] (5) Repeatedly introducing the reactants to realize a cycle of the deposition process described in step (4) to obtain the sodium ion battery positive electrode material with the surface coated with sodium aluminate.
[0046] In a second aspect, the present invention provides a positive electrode material for a sodium ion battery, wherein the positive electrode material for a sodium ion battery is prepared by the preparation method described in the first aspect.
[0047] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material as described in the second aspect.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The present invention realizes coating in a gas phase atmosphere through atomic layer deposition technology, thereby avoiding the damage of the aqueous coating method to the positive electrode material of the sodium ion battery. The entire deposition process is not only simple and controllable, but also highly controllable, green and pollution-free. The thickness of the coating layer can be regulated at the nanometer level. The prepared sodium aluminate coating layer has better quality, high uniformity and density, and higher conductivity than the traditional alumina coating layer. It can provide mechanical protection for material particles without affecting the surface deintercalation of sodium ions, prevent the release of sodium ions and the embedding of water in the material, and improve the cycle performance of the material. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] The core of the sodium ion battery positive electrode material described in the following embodiments and comparative examples is NaMnO2. The description of the core is only for a more complete explanation of the technical solution of the present invention and should not be regarded as a specific limitation of the present invention.
[0052] Example 1
[0053] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0054] (1) heating trimethylaluminum at 25° C. to obtain a trimethylaluminum vapor precursor; heating sodium tert-butoxide at 170° C. to obtain a sodium tert-butoxide vapor precursor; heating pure water at 100° C. to obtain water vapor;
[0055] (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 235° C., evacuating the chamber, and then introducing a trimethylaluminum vapor precursor into the reaction chamber at a flow rate of 30 sccm for 1 second, and then introducing nitrogen at a flow rate of 60 sccm for purging for 30 seconds;
[0056] (3) After the purge in step (2) was completed, sodium tert-butoxide vapor precursor was introduced at a flow rate of 30 sccm for 2 s, and then nitrogen was introduced at a flow rate of 60 sccm for 30 s;
[0057] (4) After the purge in step (3) is completed, water vapor is introduced at a flow rate of 30 sccm for 2 seconds, and then nitrogen is introduced at a flow rate of 60 sccm for 30 seconds to complete a deposition process;
[0058] (5) Repeat the introduction of reactants to realize the cycle of the deposition process described in step (4), and repeat the cycle until the surface is coated with sodium aluminate with a thickness of 30 nm to obtain the sodium ion battery positive electrode material.
[0059] Example 2
[0060] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0061] (1) heating dimethylaluminum isopropoxide at 40° C. to obtain a dimethylaluminum isopropoxide vapor precursor; heating sodium acetoacetate at 180° C. to obtain a sodium acetoacetate vapor precursor; and heating pure water at 105° C. to obtain water vapor;
[0062] (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 250° C., evacuating the chamber, and then introducing dimethylaluminum isopropoxide vapor precursor into the reaction chamber at a flow rate of 20 sccm for 2 seconds, and then introducing nitrogen at a flow rate of 70 sccm for purging for 20 seconds;
[0063] (3) After the purge in step (2) was completed, sodium acetoacetate vapor precursor was introduced at a flow rate of 30 sccm for 1 s, and then nitrogen was introduced at a flow rate of 40 sccm for purging for 40 s;
[0064] (4) After the purge in step (3) was completed, water vapor was introduced at a flow rate of 20 sccm for 3 seconds, and then nitrogen was introduced at a flow rate of 70 sccm for 20 seconds to complete a deposition process;
[0065] (5) Repeat the introduction of reactants to realize the cycle of the deposition process described in step (4), and repeat the cycle until the surface is coated with sodium aluminate with a thickness of 60 nm to obtain the sodium ion battery positive electrode material.
[0066] Example 3
[0067] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0068] (1) heating trimethylaluminum at 20° C. to obtain a trimethylaluminum vapor precursor; heating sodium tert-butoxide at 160° C. to obtain a sodium tert-butoxide vapor precursor; heating pure water at 98° C. to obtain water vapor;
[0069] (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 210° C., evacuating the chamber, and then introducing a trimethylaluminum vapor precursor into the reaction chamber at a flow rate of 30 sccm for 0.5 s, and then introducing nitrogen at a flow rate of 40 sccm for purging for 40 s;
[0070] (3) After the purge in step (2) was completed, sodium tert-butoxide vapor precursor was introduced at a flow rate of 40 sccm for 3 seconds, and then nitrogen was introduced at a flow rate of 70 sccm for 20 seconds;
[0071] (4) After the purge in step (3) is completed, water vapor is introduced at a flow rate of 40 sccm for 1 second, and then nitrogen is introduced at a flow rate of 40 sccm for 40 seconds to complete a deposition process;
[0072] (5) Repeat the introduction of reactants to realize the cycle of the deposition process described in step (4), and repeat the cycle until the surface is coated with sodium aluminate with a thickness of 15 nm to obtain the sodium ion battery positive electrode material.
[0073] Example 4
[0074] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1 except that the temperature of the atomic layer deposition reaction chamber in step (2) is 200° C.
[0075] Example 5
[0076] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1 except that the temperature of the atomic layer deposition reaction chamber in step (2) is 260° C.
[0077] Example 6
[0078] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1 except that the nitrogen flow rate during the purging is 30 sccm.
[0079] Example 7
[0080] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1 except that the nitrogen flow rate during the purging is 80 sccm.
[0081] Example 8
[0082] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1, except that no purging is performed in step (2) and step (3).
[0083] Example 9
[0084] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1 except that no purging is performed in steps (2) to (4).
[0085] Example 10
[0086] The present embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1, except that a trimethylaluminum vapor precursor, a sodium tert-butoxide vapor precursor, and water vapor are introduced into the reaction chamber together, and a purge is performed after all reactants are introduced.
[0087] Embodiment 11
[0088] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The preparation method is the same as that of Embodiment 1, except that water vapor is first introduced into the atomic layer deposition reaction chamber, and then the trimethylaluminum vapor precursor in step (2) and the sodium tert-butoxide vapor precursor in step (3) are introduced.
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0091] (1) heating sodium aluminate at 235° C. to obtain sodium aluminate gas;
[0092] (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 235° C., evacuating the chamber, and then introducing sodium aluminate gas into the reaction chamber for 5 seconds, and then introducing nitrogen gas at a flow rate of 60 sccm for purging for 30 seconds to complete a deposition process;
[0093] (3) Repeat the introduction of reactants to realize the cycle of the deposition process described in step (2), and repeat the cycle until the surface is coated with sodium aluminate with a thickness of 30 nm to obtain the sodium ion battery positive electrode material.
[0094] Comparative Example 2
[0095] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0096] The core of the sodium ion battery positive electrode material, sodium metaaluminate and water are mixed according to the formula, and then filtered and dried to obtain the sodium ion battery positive electrode material.
[0097] The sodium ion battery positive electrode material obtained in the above embodiments and comparative examples was prepared into a positive electrode sheet, and then prepared into a sodium ion battery with a sodium sheet, and its cycle retention rate of 200 cycles was tested, and the test results are shown in the following table; the test method of the cycle performance is: at a temperature of 25°C, the battery is first charged at a constant current of 0.1C to a voltage of 4.0V, charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 0.1C to a voltage of 2.0V; further charged at a constant current of 0.5C to a voltage of 4.0V, and then discharged at a constant current of 0.5C to a voltage of 2.0V, which is a charge and discharge cycle process; according to the above method, the charge and discharge are cycled 200 times, the discharge capacity at the time of 200 cycles is detected, and the capacity retention rate is obtained by dividing it by the first discharge capacity.
[0098] Table 1
[0099]
[0100]
[0101] From the above table we can see that:
[0102] It can be seen from Example 1 and Comparative Example 1 that the in-situ deposition of the sodium aluminate coating layer prepared by the present invention is more uniform and dense, the coating layer is more stable, and the physical phase structure is good, compared with directly using sodium aluminate as a precursor for deposition, so the obtained coating layer is more uniform and dense, the coating layer is more stable, and the physical phase structure is good, so the obtained battery has excellent cycle performance; It can be seen from Example 1 and Comparative Example 2 that the atomic layer deposition coating method described in the present invention does not destroy the structural stability of the positive electrode material of the sodium ion battery compared with liquid phase coating, and the obtained battery has excellent cycle performance; It can be seen from Example 1 and Examples 4-7 that the temperature of the atomic layer deposition reaction chamber and the flow rate of nitrogen purge will affect the atomic layer deposition process, thereby affecting the uniformity of the deposition and the bonding strength between the coating layer and the core; It can be seen from Example 1 and Examples 8-9 that the present invention can improve the deposition effect by purging nitrogen after the reaction gas is introduced, thereby improving the cycle performance of the battery; It can be seen from Example 1 and Examples 10-11 that the order in which the gas reactants are introduced in the present invention will also affect the deposition effect.
[0103] In summary, the present invention provides a sodium ion battery positive electrode material and a preparation method and application thereof. The preparation method uses atomic layer deposition for coating modification, does not involve an aqueous phase, and can precisely control the thickness of the coating at the nanometer level. Compared with other coating methods, the obtained coating layer has high uniformity and high bonding strength with the core, which can significantly improve the cycle performance of the sodium ion battery positive electrode material.
[0104] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The preparation method comprises the following steps: (1) placing a core of a sodium ion battery positive electrode material in an atomic layer deposition reaction chamber, introducing an aluminum source gas phase precursor, a sodium source gas phase precursor and water vapor into the reaction chamber for atomic layer deposition, and completing a deposition process; the core comprises a layered transition metal oxide; The temperature of the atomic layer deposition reaction chamber is 210-250°C; The order of introducing is to first introduce the aluminum source gas phase precursor, then introduce the sodium source gas phase precursor, and finally introduce water vapor; The aluminum source gas phase precursor is obtained by heating an aluminum source, and the aluminum source includes trimethylaluminum and / or dimethylaluminum isopropoxide; The sodium source gas phase precursor is obtained by heating a sodium source, and the sodium source includes sodium tert-butoxide or sodium acetoacetate; (2) Repeatedly introducing the reactants to realize a cycle of the deposition process described in step (1) to obtain the sodium ion battery positive electrode material with the surface coated with sodium aluminate.
2. The preparation method according to claim 1, characterized in that: Step (1) The reaction chamber is evacuated before the gas is introduced into the reaction chamber.
3. The preparation method according to claim 1 or 2, characterized in that: After the aluminum source gas phase precursor is introduced in step (1), it is purged and then the sodium source gas phase precursor is introduced.
4. The preparation method according to claim 1 or 2, characterized in that: In step (1), after the sodium source gas phase precursor is introduced, it is purged and then water vapor is introduced.
5. The preparation method according to claim 1 or 2, characterized in that: After the water vapor is introduced in step (1), a purge is also performed.
6. The preparation method according to claim 5, characterized in that: The purge gas used for the purge includes nitrogen.
7. The preparation method according to claim 5, characterized in that: The purge gas flow rate is 40-70 sccm.
8. The preparation method according to claim 5, characterized in that: The purging time is 20-40s.
9. The preparation method according to claim 1 or 2, characterized in that: The water vapor in step (1) is obtained by heating pure water at 98-105°C.
10. The preparation method according to claim 1 or 2, characterized in that: The water vapor introduction time in step (1) is 1-3 s, and the introduction flow rate is 20-40 sccm.
11. The preparation method according to claim 1 or 2, characterized in that: The aluminum source gas phase precursor in step (1) is obtained by heating an aluminum source at 20-40°C.
12. The preparation method according to claim 1 or 2, characterized in that: In step (1), the aluminum source gas phase precursor is introduced for a time of 0.5-2 s and at a flow rate of 20-40 sccm.
13. The preparation method according to claim 1 or 2, characterized in that: The sodium source gas phase precursor in step (1) is obtained by heating a sodium source at 160-180°C.
14. The preparation method according to claim 1 or 2, characterized in that: The sodium source gas phase precursor is introduced for a time of 1-3 s and an introduction flow rate of 20-40 sccm in step (1).
15. The preparation method according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) heating an aluminum source at 20-40°C to obtain an aluminum source vapor precursor; heating a sodium source at 160-180°C to obtain a sodium source vapor precursor; heating pure water at 98-105°C to obtain water vapor; The aluminum source includes trimethylaluminum and / or dimethylaluminum isopropoxide; the sodium source includes sodium tert-butoxide or sodium acetoacetate; (2) placing the core of the sodium ion battery positive electrode material in an atomic layer deposition reaction chamber at a temperature of 210-250°C, evacuating the chamber, and then introducing an aluminum source gas phase precursor into the reaction chamber at a flow rate of 20-40 sccm for 0.5-2 seconds, and then introducing nitrogen at a flow rate of 40-70 sccm for purging for 20-40 seconds; The inner core comprises a layered transition metal oxide; (3) After the purge in step (2) is completed, a sodium source gas precursor is introduced at a flow rate of 20-40 sccm for 1-3 seconds, and then nitrogen is introduced at a flow rate of 40-70 sccm for purging for 20-40 seconds; (4) After the purge in step (3) is completed, water vapor is introduced at a flow rate of 20-40 sccm for 1-3 seconds, and then nitrogen is introduced at a flow rate of 40-70 sccm for purging for 20-40 seconds to complete a deposition process; (5) Repeatedly introducing the reactants to realize a cycle of the deposition process described in step (4) to obtain the sodium ion battery positive electrode material with the surface coated with sodium aluminate.
16. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material is prepared by the preparation method according to any one of claims 1 to 15.
17. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material as claimed in claim 16.
Citation Information
Patent Citations
Preparation method for positive electrode material, positive electrode material and lithium ion battery
CN111010887A
Modified positive electrode material and preparation method and application thereof
CN115432751A